Augmentation Pressure Is Influenced by Ventricular Contractility/Relaxation Dynamics: Novel Mechanism of Reduction of Pulse Pressure by Nitrates - Fok, Henry; Guilcher, Antoine; Li, Ye; Brett, Sally; Shah, Ajay; Clapp, Brian; Chowienczyk, Phil (Hypertension (Dallas, Tex. 1979), 2014)
Augmentation pressure (AP), the increment in aortic pressure above its first systolic shoulder, is thought to be determined mainly by pressure wave reflection but could be influenced by ventricular ejection characteristics. We sought to determine the mechanism by which AP is selectively reduced by nitroglycerin (NTG). Simultaneous measurements of aortic pressure and flow were made at the time of cardiac catheterization in 30 subjects (11 women; age, 61±13 years [mean±SD]) to perform wave intensity analysis and calculate forward and backward components of AP generated by the ventricle and arterial tree, respectively. Measurements were made at baseline and after NTG given systemically (800 μg sublingually, n=20) and locally by intracoronary infusion (1 μg/min; n=10). Systemic NTG had no significant effect on first shoulder pressure but reduced augmentation (and central pulse pressure) by 12.8±3.1 mm Hg ( P <0.0001). This resulted from a reduction in forward and backward wave components of AP by 7.0±2.4 and 5.8±1.3 mm Hg, respectively (each P <0.02). NTG had no significant effect on the ratio of amplitudes of either backward/forward waves or backward/forward compression wave energies, suggesting that effects on the backward wave were largely secondary to those on the forward wave. Time to the forward expansion wave was reduced ( P <0.05). Intracoronary NTG decreased AP by 8.3±3.6 mm Hg ( P <0.05) with no significant effect on the backward wave. NTG reduces AP and central pulse pressure by a mechanism that is, at least in part, independent of arterial reflections and relates to ventricular contraction/relaxation dynamics with enhanced myocardial relaxation.